Inflation : theory & policy - Hagger, A.J. (London : Macmillan Press Ltd., 1977)
The aim of this book is to give a comprehensive treatment of the problem of inflation. The author tried to safeguard the interests of this group by making the empirical, econometric discussion as non-technical as possible and by including a brief account of basic econometric method in Section 4.1 for the benefit of the entirely uninitiated.
Includes bibliographical references and index.
osa 08/08/18
Loans
Keywords: Inflation policy; Wage-price policy